SPEAK CLEARLY, TEACH CONFIDENTLY: EVALUATING PRAAT SOFTWARE IN PRONUNCIATION INSTRUCTION FOR EFL LEARNERS - Suyudi, Ichwan; Wibowo, Agung Prasetyo; Ali, Ahmad Juma Khatib Nur (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
The researcher aims to determine the effectiveness of the use of Praat software to enhance the teaching of pronunciation and phonology among first year student in English Literature, in a private university in Jakarta. This research through descriptive qualitative method was concerned with acoustic analysis of students producing vowel contrasts, sentence-level intonation and patterns of lexical stress: formant measures (F1 and F2), pitch contour tracking and comparisons of stress durations. A group of 15 students were subjected to a guided pronunciation guided task and their recording files were examined and linked with those of the native speakers through Praat. It was found that despite the different levels of precise results that the students demonstrated, the visual graphic provided by Praat greatly enhanced their understanding of the segmental and suprasegmental errors. Although the software was incidentally not very well received at the first interpretation of the acoustic data, the students liked it. The fact that the study is integrative in its design - it deals with vowel quality, intonation and word stress, gives a global look at the topic of pronunciation training. The findings of this paper indicate that Praat is an excellent Computer-Assisted Pronunciation Training (CAPT) program which fills the gap between theoretical aspects of phonology and practice. This paper suggests the inclusion of Praat-based tasks into the curriculum more explicitly to promote individual contact, learner ownership and long-term pronunciation work